(untitled) (Agriculture Development Journal, 2022)
Study on limnology of Thosne River was done to identify the diversity of aquatic insect and fish, and also to determine the water quality parameters for assessing suitability for fish farming. Some water quality parameters were recorded on the spot and others were analyzed in the laboratory. Altogether 14 different limnological parameters (3 physical, 8 chemical, 2 biological and 1 geographical) of Thosne river were studied in winter and spring seasons. During study period, the water temperature at the 1st (downstream) and the 5th (upstream) sampling stations ranged from: 15.75±2.81°C and 12.29±2.61°C: the pH 7.59±0.22 and 6.37±0.23; conductivity 194±10.7 μS/cm and 130±12 μS/cm; turbidity 5.91±2.74 NTU and 2.75±1.89 NTU, dissolved oxygen 9.62±0.87 mg/L and 10.58±0.7 mg/L; hardness 86.70±10.86 mg/L and 60.54±8.9 mg/L; chloride 14.25±25 mg/L and 7.79±1.44 mg/L; and flow rate 22.47±3.5 L/Sec and 13.5±2.4 L/Sec respectively. The ammonia nitrogen at the 1st (downstream), 3rd (midstream) and 5th (upstream) sampling stations ranged from 0.19±0.07; mg/L, 0.031±0.0056 mg/L and 0.013±0.003 mg/L whereas nitrate nitrogen ranged from 2.20±0.84 mg/L, 0.50±0.10 mg/L and 0.17±0.060 mg/L respectively. All the parameters were positively correlated with each other except dissolved oxygen and altitude. Three native fish species and aquatic insects from eight different families were identified. All the water quality parameters were within the recommended limit for rainbow trout fish farming up to midstream.